Development of programmable logic controllers training kit - Aqel, Mohammad O. A.; Ismail, Napsiah (2005)
Programmable Logic Controllers (PLCs) have become the main workhorse for equipment control in a variety of industries since they were introduced in 1968. PLC’s are widely used in industrial applications to control robots, conveyors, electric motors, electro pneumatic and electro hydraulic systems. In a time of rapid technological innovation in the field of PLC, practical training in PLC control is needed to help cope with these changes and it is critical for the engineer to have a good working knowledge of its operating principles and terminology. This paper describes the development of PLC Training Kit as an educational tool to enable the trainees to familiarize themselves with PLC hardware and programming principles, and PLC control circuit design. Soft-prototype and experiment courseware have been designed to help the instructors in lecturing a well organized PLC lab course and enable the trainees to simulate many industrial control applications. Each Soft- Prototype is a ‘virtual machine or online simulation’ and the simulation runs on the PC and communicates serially with the PLC.